Education in the Anthropocene: From Theorists towards Young Climate Activists - Kairė, Sandra (Acta Paedagogica Vilnensia, 2021)
This paper continues the scientific discussion on education in the Anthropocene and focuses on the complexity of future education from the learner’s perspective. The first part of the paper explores proposals for education in the Anthropocene from the posthumanist perspective, based on the critical remarks and ideas of different theorists, such as Annette Gough, Nathan Snaza, and Brad Petitfils. The second part focuses on the children of the Anthropocene as the reality of today’s education. The third part looks at the case of young climate activists, who can be considered to be children of the Anthropocene, and how their relationship with education is changing. Young climate activists experience doubts, distrust, and disappointment over formal education, its practice, and its future. Therefore, climate activism movements can be treated as a unique learning environment for young people that also compensates what children of the Anthropocene are missing in formal education.